(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This article explores an area of graphic design and social design that highlights graphic pieces in public settings, circulating in spaces of social exclusion to generate an exchange between a disabled person and a bystander, due to the economic scarcity of the communicators in a situation of poverty. A preliminary has enabled the creation of a corpus of visual materials, mainly printed, ranging from handwritten or scribbled notes, to printed materials for soliciting alms due to economic hardship and the specific issue of deafness. They are conveyed through popular sign and printed symbol systems that accompany this type of visual language. To address these practices, we use a qualitative methodology, while acknowledging the need for critical discussion about the extent to which methodologies are appropriate or even possible in such fragile contexts of care. We emphasize a form of visual testimony that this research defines as graphics of silence, based on material evidence emerging from precarious conditions. This reflection and proposal aim to document a circuit of graphics that emerge from a subaltern position, motivated by the need for donations within a transactional exchange. These materials lie beyond the usual territories of academic and professional design and are thus considered as legitimate objects of study from a situated perspective.